Levels of protein hydroperoxides and carbonyl groups in guinea pigs native of high altitudes (Huancavelica, 3660 m) - Huayta, Roxana (2013)
The influence of hypobaric hypoxia on protein oxidation in lungs, heart, liver, kidneys and testicles of high altitude native guinea pigs (Huancavelica, 3660 m) in comparison to sea level (Lima, 150 m) native guinea pigs was evaluated. The concentration of protein hydroperoxides (POOH) and carbonyl groups (GC) as markers of protein oxidation, as well as total thiols (TT) concentration, powerful reducing agents that act as live antioxidants were determined. The results showed low concentration of GC in high altitude guinea pig testicles, as compared to what was found at sea level. POOH low concentration was also found in high altitude guinea pig heart with respect to that found at sea level. TT concentration was lower in high altitude heart and lungs in relation to the concentrations found at sea level. Contrary to these results, higher concentrations of POOH in high altitude guinea pig liver and testicles were found, while increase in TT is observed only in the high altitude guinea pig kidneys. These results show that the hypobaric hypoxia selectively influences on the oxidation of proteins and on endogenous nonenzymatic antioxidant response.